Sosialisasi Produk BSI Akad wadiah dalam Tabungan Haji bagi Masyarakat desa Pagar Banyu Kota Pagar Alam Provinsi Sumsel - Rahmansyah Rahmansyah; Nurul Hak; Rahmat Putra Hasibuan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of Islamic finance in Indonesia shown significant growth as alternative financial system based Islamic principles. Data from Bank Syariah Indonesia (BSI) shows the number of Hajj savings accounts reached 5.5 million accounts as of November 2024 and increased to 6.33 million in July 2025. This growth reflects the high level of public enthusiasm in preparing for Hajj funds early on through Islamic financial institutions. In various regions of South Sumatra, BSI has become one of the institutions widely used by the public to open Hajj savings accounts due to its service network and ease of access. The village of Pagar Banyu has great potential for increasing the use of Sharia-based Hajj savings, particularly through the dissemination of information about BSI products. Through appropriate outreach activities, the public can understand wadiah contracts, the benefits of hajj savings, and the process of opening an account and registering for a hajj quota. In this context, Bank Syariah Indonesia (BSI) plays an important role as it is one of the largest Islamic banks. The target audience for this outreach activity is the general public in Pagar Banyu Village, Pagaralam City, South Sumatra Province. This study aims to improve Islamic financial literacy among people Pagar Banyu Village, particularly regarding Hajj savings at BSI, by providing practical understanding of how to open a Hajj savings account, requirements, procedures, and benefits, and encouraging community to start planning for pilgrimage by saving gradually and building awareness of importance of managing finances in accordance with Islamic principles.